PACKAGING LOCAL WISDOM-BASED RIVER TOUR - I Gusti Ketut Purnaya; I Nengah Laba; I Made Trisna Semara (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2019)
The rapid development of today's technology encourages every component in the government create a new idea. The government of Denpasar has implemented smart city program by triggering tour package of Denpasar City tour. However, in the arrangement of the Badung River as a tourist attraction by the government of Denpasar is not yet optimaliced in developing its tourism. The potency has not been able to attract tourists to visit the Badung River as a new tourist attraction. Therefore, it needs an effort to develop a river tour package to preserve the local wisdom so that it remains sustainable. The purpose of this research is to plan a river tour through the development of local wisdom-based travel packages in Badung river. This research uses mix method. Data collection is done using interview techniques, observations, and documentation studies. The data analysis used in this research is internal factor analysis using IFAS, external factor analysis using EFAS, and SWOT analysis. The results showed that the growth strategy can be designed by maintaining the local culture and wisdom. It is further developed by planning a tour package of the River Tour which has been tailored to the needs and desires of tourists.